The complete Peanuts, 1959 to 1960 - Schulz, Charles M. (Charles Monroe), 1922-2000. (New York : Distributed to the book trade by W.W. Norton, 2006)
Contains a collection of Charles M. Schulz's "Peanuts" comic strips, covering the years 1959-1960. Includes an introduction by Whoopi Goldberg.
Includes index.
Young Adult
Keywords: Brown, Charlie (Fictitious character) -- Fiction; Children -- Fiction; Snoopy (Fictitious character) -- Fiction; Brown, Charlie (Fictional character) -- Fiction; Children -- Fiction; Comic books, strips, etc; Snoopy (Fictional character) -- Fiction